(untitled) (Journal of Fatima Jinnah Medical University, 2018)
To assess the outcome in comminuted distal radius fractures with closed K-wires reduction and ORIF with T-Plate and bone graft Study Design: It was a prospective, comparative study. Place and Duration of Study: in 2010 at department of orthopedics, Lahore General Hospital,Lahore Material and Methods: Thirty patients were included and treated in two groups; One group was treated with closed reduction and percutaneous K-.wires fixation with pop cast while second group was treated with ORIF with T-Plate and bone graft. Results: Average anesthesia time in group A was about 30.75 minutes and operative time was about 20.5 minutes. In group B average anesthesia time was about 39.5 minutes and operative time was about 32.5 minutes. Average hospital stay in group A was1 day and in group B was 2 days. All fractured healed well eventually. Dorsal angulations and range of motion did not differ significant ally on follow up. Conclusion: Treatment of distal communated radius fractures can be done percutaneously or ORIF without significant morbidity